PENGARUH PENGGUNAAN TEKNIK MELENGKAPI PARAGRAF TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS VIII SMP NEGERI 1 SUTERA KABUPATEN PESISIR SELATAN - Saltia, Deppa; Asr, Yasnur; DN, Upit Yulianti (Pendidikan Bahasa Indonesia, 2014)
The problem in this study is the lack of students interest in reading comprehension and the learning technique which was used by the teachers is not very effective. The purpose of this study is to describe the effect of the use of complementary techniques to the ability of reading comprehension skill of is the students of junior high school sutera kabupaten pesisir selatan grade VIII. The type of this research is the qualitative research with experimental design. The population of this research is the students of junior high school sutera kabupaten pesisir selatan grade 8 year 2013/2014 with 287 students in total. The sample of this research is grade VIII 1 with 32 students, by using purposive sampling. The research data is the test result of reading comprehension of grade VIII 1 before and after using the paragraph completion. Based on the analysis, the data showed the reading comprehension skill of is the students of junior high school sutera kabupaten pesisir selatan grade VIII 1 are as followed. First, the reading comprehension skill of grade VIII 1 before using the paragraph completion has the mean of 64.04, with the range 56-65% with enough qualification. Second, the reading comprehension skill of skill of grade VIII 1 by using paragraph completion have the mean 71,25 with 66-75% qualification. Third, there is the influence of the reading comprehension skill of students grade VIII 1 with paragraph completion technique because t hitung(2,59) is bigger than t table (1,70) on the significant 95% and dk=n-2.